Process control: An application in the packaging of Concholepas concholepas - Romaina Flores, Juan Carlos (2021)
The research was carried out in an industrial production and packaging export company of Concholepas concholepas located in the city of Tacna, Peru. Two quality variables that have relevance in the final product were determined, the volume of the container and the percentage proportion of proteins in the unit. After that, the means end analisys diagram was finished, for the variable volume in 452,356 g as average of the process, with upper control limits of 454,514 g and lower limit of 450,198 g. In regard to its range, the central line or average of the range was established at 3.74167 g with an upper control limit of 7.91171 g and a lower limit of 0.0 g. For the proportion of proteins, an average proportion of 15.24% was observed with upper and lower control limits of 16.40% and 14.08. Concerning its range diagram, an average range of 2.0% was found, with an upper control limit of 4.25% and a lower control limit of 0.0%. In the control diagrams, it is observed that the process in production with respect to volume and the proportion of proteins in the packaged product is in statistical control since all the scores obtained are within the limits of quality control.